Robotic guide system for insertion of screws in spinal fixation surgery - Muñoz Rodríguez, P. E.; Vivas Albán, A. (Revista Mexicana de Ingenieria Biomedica, 2015)
This article presents the design and operation of the first prototype of a robot, designed to guide the insertion of screws in spinal fixation surgery. This type of surgery, usually done manually, could cause many injuries due to human error at the moment of inserting the screws into the patient?s vertebrae. Computed tomography can be used to avoid such errors, but the results are much better if a robot assists and indicates the surgeon the path for the insertion of the screw, according to the image scanner. This article shows how using a commercial low-cost robot can be implemented in a system that provides a practical solution to thisproblem. A software that allows you to define the start and the end positions of the screw to be introduced on the Dicom image of the patient, was implemented. With this information the system moves the robot which has a ring that will guide the surgeon in the final insertion. The results show a fairly accurate system, giving the surgeon a safe path of insertion.